2010
DOI: 10.1055/s-0031-1278380
|View full text |Cite
|
Sign up to set email alerts
|

Arteritic anterior ischemic optic neuropathy treated with intravenous prostaglandin E1and steroids

Abstract: Arteritic anterior ischemic optic neuropathy (AAION) is an acute ischemia of the posterior ciliary arteries and/or ophthalmic artery due to inflammation. Therapy is immediate intervention with systemic steroids, especially to protect against vision loss in the other eye. The addition of a potent vasodilator to the steroids could help restore ocular blood flow and improve visual acuity. The objective of the current report was to present the use of prostaglandin E(1) (PGE(1)) - a powerful vasodilator of the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Previous reports successfully treated one case of acute branch RAO with a daily dose of 140 lg of PGE1 for 2 days, 37 and two cases of arteritic anterior ischemic optic neuropathy with a daily dose of 80 lg of PGE1 for 2 days. 38 The current study suggested that, in cases with acute CRAO, a daily dose of 80 lg of PGE1 may be sufficient to dilate the retinal vessels, but this may depend on other factors, such as body weight. Regarding the side effects with venous injection of PGE1, based on the information provided by the postmarket product surveillance in Japan (the information found on the manufacturer's home page: http:// www.ono.co.jp/eng/index.html), frequencies of angialgia, vomiting, and skin trouble are at 0.5% to 5.0% incidence, of systemic hypotension is rare at less than 0.5% incidence, and local or systemic bleeding is very rare at less than 0.05% incidence; the incidences of side effects are expected to be five times fewer with oral PGE1 than venous injection.…”
Section: Discussionmentioning
confidence: 69%
“…Previous reports successfully treated one case of acute branch RAO with a daily dose of 140 lg of PGE1 for 2 days, 37 and two cases of arteritic anterior ischemic optic neuropathy with a daily dose of 80 lg of PGE1 for 2 days. 38 The current study suggested that, in cases with acute CRAO, a daily dose of 80 lg of PGE1 may be sufficient to dilate the retinal vessels, but this may depend on other factors, such as body weight. Regarding the side effects with venous injection of PGE1, based on the information provided by the postmarket product surveillance in Japan (the information found on the manufacturer's home page: http:// www.ono.co.jp/eng/index.html), frequencies of angialgia, vomiting, and skin trouble are at 0.5% to 5.0% incidence, of systemic hypotension is rare at less than 0.5% incidence, and local or systemic bleeding is very rare at less than 0.05% incidence; the incidences of side effects are expected to be five times fewer with oral PGE1 than venous injection.…”
Section: Discussionmentioning
confidence: 69%
“…9B). Interestingly, PGE and PGE analogs are currently used for the treatment of various ocular pathologies, including glaucoma and ischemia (Steigerwalt et al, 2010;Alm, 2014). Since AKR inhibitors have been envisaged as potential therapeutic tools for ocular diabetic complications, the definition of PGs as inhibitors of AKR1B1 encourages the study of their potential usefulness for these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…PGE1 given intravenously at a dose of 1 μg/kg together with steroids has been successfully used to treat cases of NA-PION and acute non-arteritic anterior ischemic optic neuropathy (NA-AION) (4,5,8). PGE1 has helped in the treatment of acute arteritic anterior ischemic optic neuropathy when given with high-dose steroids (9). In the current case, intravenous PGE1 and steroids were immediately started as soon as the patient was diagnosed with NA-PION, resulting in an improvement in visual fields and visual acuity.…”
Section: Discussionmentioning
confidence: 99%